2017
DOI: 10.1002/ps.4708
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial distribution of insecticide‐resistance mutations in the green peach aphid Myzus persicae (Hemiptera: Aphididae) on primary and secondary host plants in central Chile

Abstract: This study provides farm-scale evidence that weeds are not an important reservoir of the R allele, but they are for the S allele. Hence, the presence of heterozygous genotypes on peach trees is most likely attributable to weeds. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
(81 reference statements)
1
10
0
Order By: Relevance
“…Similar patterns have been previously described in Greece (Margaritopoulos et al, 2000(Margaritopoulos et al, , 2002Zitoudi et al, 2001;Poupoulidou et al, 2006;Blackman et al, 2007), Italy (Margaritopoulos et al, 2003), Japan Takada, 2003, 2004;Margaritopoulos et al, 2007aMargaritopoulos et al, , 2007b and the USA (Harlow and Lampert, 1990;Clements et al, 2000aClements et al, , 2000bSrigiriraju et al, 2009), where higher genotype diversity of tobacco aphids has been observed (Zepeda-Paulo et al, 2010). The colour polymorphisms can be explained by the presence of new M. persicae nicotianae genotypes resulting from sexual reproduction events, as reported for M. persicae in Chile on peaches (Rubiano-Rodríguez et al, 2014, 2019Rubio-Meléndez et al, 2018) or by new introduction events from neighbouring countries. These putative new genotypes could possess insecticide resistance mutations that affect tobacco aphid control in tobacco fields in Chile.…”
Section: Introductionsupporting
confidence: 83%
“…Similar patterns have been previously described in Greece (Margaritopoulos et al, 2000(Margaritopoulos et al, , 2002Zitoudi et al, 2001;Poupoulidou et al, 2006;Blackman et al, 2007), Italy (Margaritopoulos et al, 2003), Japan Takada, 2003, 2004;Margaritopoulos et al, 2007aMargaritopoulos et al, , 2007b and the USA (Harlow and Lampert, 1990;Clements et al, 2000aClements et al, , 2000bSrigiriraju et al, 2009), where higher genotype diversity of tobacco aphids has been observed (Zepeda-Paulo et al, 2010). The colour polymorphisms can be explained by the presence of new M. persicae nicotianae genotypes resulting from sexual reproduction events, as reported for M. persicae in Chile on peaches (Rubiano-Rodríguez et al, 2014, 2019Rubio-Meléndez et al, 2018) or by new introduction events from neighbouring countries. These putative new genotypes could possess insecticide resistance mutations that affect tobacco aphid control in tobacco fields in Chile.…”
Section: Introductionsupporting
confidence: 83%
“…Such a strong linkage between MACE and s‐kdr (M918L) mutations has also been demonstrated in France 21 . Linkage disequilibrium between MACE and kdr and/or s‐kdr (M918T) mutations was also shown in UK, 13 Greece 43 and Chile 50 on some samples from secondary hosts (tobacco, weeds, sweet pepper) but not on samples from peach orchards 43,50 . As aphids from peach consist mostly of sexual genotypes, recombination might break such linkages.…”
Section: Discussionmentioning
confidence: 90%
“…21 Linkage disequilibrium between MACE and kdr and/or s-kdr (M918T) mutations was also shown in UK, 13 Greece 43 and Chile 50 on some samples from secondary hosts (tobacco, weeds, sweet pepper) but not on samples from peach orchards. 43,50 As aphids from peach consist mostly of sexual genotypes, recombination might break such linkages. However, the possibility that the MACE-kdr linkage comes from an interaction between these mutations on fitness cost cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, numerous insecticides are used to control this insect and in turn, the resistance to multiple insecticides are developed 13 . The most common resistant mechanisms include target-site mutations and over-expression of detoxification enzymes 14 , 15 . In M. persicae , metabolic enzymes reported to confer resistance include esterase E4 (or the mediterranean variant FE4), giving broad-spectrum resistance to organophosphates, carbamates and pyrethroids, and cytochrome P450 CYP6CY3, conferring resistance to neonicotinoids 16 .…”
Section: Introductionmentioning
confidence: 99%